2019
DOI: 10.3389/fimmu.2018.03183
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Dietary Nutrients in Inflammatory Bowel Disease

Abstract: Inflammatory bowel disease (IBD) is a chronic and relapsing inflammatory disease of the gastrointestinal tract. Although the precise etiology of IBD remains incompletely understood, accumulating evidence suggests that various environmental factors, including dietary nutrients, contribute to its pathogenesis. Dietary nutrients are known to have an impact on host physiology and diseases. The interactions between dietary nutrients and intestinal immunity are complex. Dietary nutrients directly regulate the immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
115
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(118 citation statements)
references
References 189 publications
(216 reference statements)
0
115
0
Order By: Relevance
“…Additionally, the study of other autoimmune diseases does not help in establishing a link between diet and metabolites with their pro or anti-inflammatory effect. In Crohn's disease, for instance, animal studies suggest the potential beneficial effect of short chain fatty acids, tryptophan, arginine, and glutamine due to their roles in the modulation of the immune system, but no clinical studies have been performed to date [213]. A cross-sectional metabolomics study also found decreased levels of essential PUFA in patients with lupus, but diet was not taken into account in this study [214].…”
Section: Studies Of Beneficial Effect Of Diet In Ramentioning
confidence: 74%
“…Additionally, the study of other autoimmune diseases does not help in establishing a link between diet and metabolites with their pro or anti-inflammatory effect. In Crohn's disease, for instance, animal studies suggest the potential beneficial effect of short chain fatty acids, tryptophan, arginine, and glutamine due to their roles in the modulation of the immune system, but no clinical studies have been performed to date [213]. A cross-sectional metabolomics study also found decreased levels of essential PUFA in patients with lupus, but diet was not taken into account in this study [214].…”
Section: Studies Of Beneficial Effect Of Diet In Ramentioning
confidence: 74%
“…Consequently, host's microbiota ferment DF, resulting in the production of small organic metabolites, mainly short-chain fatty acids (SCFAs, such as acetate, propionate, and butyrate). There is a wide range of bacteria capable of fermenting DF, but according to enzymatic activity, each bacterium has a preferred substrate [100,101]. For the colonocytes, SCFAs are important energy substrates [102] and can also bind G-protein-coupled receptors (such as GPR41, GPR43, and GPR109a), acting as signaling molecules, regulating the immune responses and the differentiation of immune cells.…”
Section: Fibers and Short-chain Fatty Acidsmentioning
confidence: 99%
“…erefore, many studies also indicate the beneficial effect of o-3 above all in UC [28,29]. However, fats (in total) consumed in excess may increase the risk of both CD and UC [30]. Rapeseed oil, linseed oil, and fatty fish (e.g., salmon, mackerel, and sardines) Omega-6 Linoleic acid c-Linoleic acid Sunflower oil, grapeseed oil, and corn oil Table 1: Composition, functions, and sources of dietary fibre according to the division into fractions [9].…”
Section: E Influence Of Fats On the Development And Course Of Inflammmentioning
confidence: 99%